The Cat Who Got Carried Away - Ahlberg, Allan (London Walker, 2003)
It is an exciting couple of days for the Gaskitt family and their community, with missing pets, an unusual substitute teacher, and a special addition to their household. Suggested level: primary.
Include Illustrations
Keywords: Families